The characterization of Jesus in the Book of Hebrews - Small, Brian C. (Biblical Interpretation Series, 2014)
In The Characterization of Jesus in the Book of Hebrews Brian Small applies the tools of literary and rhetorical criticism to reconstruct the author of Hebrew's portrayal of Jesus' character. The author of Hebrews uses a variety of literary and rhetorical devices in order to develop his characterization of Jesus. The portrait that emerges is that Jesus is a person of exemplary character, who exhibits both divine and human character traits. Some of the traits reveal Jesus' greatness while others reveal his moral excellence. Jesus' exemplary character plays a prominent role in the author's argument and has profound implications for his audience. Jesus' character produces many benefits for his followers and his character entails certain obligations from his followers.